A strikingly coloured new species of Paragiopagurus Lemaitre, 1996 (Crustacea: Decapoda: Anomura: Parapaguridae) from French Polynesia - Lemaitre, Rafael; Poupin, Joseph (Zootaxa, 2003)
A new deep-water hermit crab species, Paragiopagurus fasciatus, is described from the Austral Islands, French Polynesia. This new species has a distinct colour pattern consisting of red stripes on the shield and ambulatory legs, and is also distinguished by having short antennal peduncles, strongly armed carpus of the left cheliped, and in females, laterally armed telson. This new species is the fourth of the genus, and the twelfth of the family, recorded from French Polynesia. The closest morphological affinities of P. fasciatus n. sp. are with P. bougainvillei (Lemaitre, 1994) and P. wallisi (Lemaitre, 1994), two species also known so far exclusively from French Polynesia. A taxonomically updated list of species from French Polynesia is presented.